Neoslavery Narratives of African American Political Prisoners: Subverting the Power of Writing - Maria Mercone (e-cadernos ces)
This paper aims to trace the founding elements of the carceral institution in the United States by highlighting the effects of settler culture and slavery on its rise and development. The first section will show how the evolution of the prison system in the US has been highly informed by racializing rationalities and practices connected to the global history of colonial incarceration. The second section, in contrast, will be dedicated to a close reading of a selected collection of narrative fragments written by African American political prisoners between the 1960s and 1980s, focusing on the concept of neoslavery. The ultimate objective of this paper is to demonstrate that prison has been a site of critical production of knowledge and that incarcerated activists’ contributions played a pivotal role in critiquing the interrelation of colonial incarceration, racism, and political repression.